The Relationship between Early-Life Conditions in the Home Country and Adult Outcomes among Child Immigrants in the United States - Deniz Gevrek; Z. Eylem Gevrek; Cahit Guven (Institute of Labor Economics (IZA), 2020)
We examine the impact of health and economic conditions at birth on the adult outcomes of child immigrants using the Children of Immigrants Longitudinal Study. Our sample consists of children from 39 countries who were brought to the United States before the age of 13. We estimate immigrant outcomes as a function of the infant mortality rate (IMR) and GDP per capita of their home country in the year of birth, controlling for birth-year, year-of-arrival and country-of-birth fixed effects, as well as demographic characteristics. IMR has a significant negative impact on English reading ability and GPA in middle school. IMR significantly decreases first job prestige, years of schooling, working hours, log earnings and income satisfaction. Some of these effects appear to be working through the lower middle school GPA. IMR does not influence self-rated health or labour market participation in adulthood, and there is no statistically significant relationship between GDP per capita and adult outcomes. Our estimates are of economic significance: the impact of being born in 1975 versus 1976 in Nicaragua in terms of the impact of IMR on earnings is equal to the gender effect on earnings, while the effect on income satisfaction of being born in Cuba in 1975 versus 1976 in terms of the impact of IMR is about equal to the father's high school completion effect. Our results cannot be explained by selection on observables: the pre-migration characteristics of children and parents are not associated significantly with the health and economic conditions at birth. Also, several tests show that our results cannot be explained by potential selection on unobservables. These results are robust to sample attrition and the inclusion of cohort trends and interaction effects between age-at-arrival and home country conditions.
Keywords: I14; J13; J15; J28; 330; adult outcomes United States; infant mortality; birth conditions; immigrants